Biologic Impact of Mechanical Power at High and Low Tidal Volumes in Experimental Mild Acute Respiratory Distress Syndrome. (June 2018) - Santos, Raquel S.; Maia, Ligia de A.; Oliveira, Milena V.; Santos, Cíntia L.; Moraes, Lillian; Pinto, Eliete F.; Samary, Cynthia dos S.; Machado, Joana A.; Carvalho, Anna Carolinna; Fernandes, Marcos Vinícius de S.; Martins, Vanessa; Capelozzi, Vera L.; et al.
Abstract : Background: The authors hypothesized that low tidal volume (VT ) would minimize ventilator-induced lung injury regardless of the degree of mechanical power. The authors investigated the impact of power, obtained by different combinations of VT and respiratory rate (RR), on ventilator-induced lung injury in experimental mild acute respiratory distress syndrome (ARDS). Methods: Forty Wistar rats received Escherichia coli lipopolysaccharide intratracheally. After 24 h, 32 rats were randomly assigned to be mechanically ventilated (2 h) with a combination of different VT (6 ml/kg and 11 ml/kg) and RR that resulted in low and high power. Power was calculated as energy (ΔP, L 2 /E, L ) × RR (ΔP, L = transpulmonary driving pressure; E, L = lung elastance), and was threefold higher in high than in low power groups. Eight rats were not mechanically ventilated and used for molecular biology analysis. Results: Diffuse alveolar damage score, which represents the severity of edema, atelectasis, and overdistension, was increased in high VT compared to low VT, in both low (low VT : 11 [9 to 14], high VT : 18 [15 to 20]) and high (low VT : 19 [16 to 25], high VT : 29 [27 to 30]) power groups. At high VT, interleukin-6 and amphiregulin expressions were higher in high-power than in low-power groups. At high power, amphiregulin and club cell protein 16 expressions were higher in high VT than in low VT . Mechanical energy and power correlated well with diffuse alveolar damage score and interleukin-6, amphiregulin, and club cell protein 16 expression. Conclusions: In experimental mild ARDS, even at low VT, high mechanical power promoted ventilator-induced lung injury. To minimize ventilator-induced lung injury, low VT should be combined with low power. Abstract : In an in vivo study of experimental acute respiratory distress syndrome, different combinations of tidal volume and respiratory rate were used to demonstrate that mechanical power and tidal volume can independently contribute to ventilator-induced lung injury.Supplemental Digital Content is available in the text.